A single gene of a commensal microbe affects host susceptibility to enteric infection - Mi Young Yoon (Nature Portfolio, 2016)
The interactions between gut bacteria and enteric pathogens are poorly understood. Here, Yoon et al. show that subinhibitory antibiotic treatment in a mouse model leads to overgrowth of an E. coli strain carrying a catalase-encoding gene that enhances infection with the human pathogen Vibrio cholerae.